2009
DOI: 10.1007/s10404-009-0510-x
|View full text |Cite
|
Sign up to set email alerts
|

Interfacing microfluidics to LDI-MS by automatic robotic spotting

Abstract: We developed a method of interfacing microfluidics with mass spectrometry (MS) using a robotic spotting system to automate the contact spotting process. We demonstrate that direct and automated spotting of analyte from multichannel microfluidic chips to a custom microstructured MALDI target plate was a simple, robust, and high-throughput method for interfacing parallel microchannels using matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS). Using thermoplastic cyclic olefin copolymer (COC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…Liquid chromatography (LC) devices were later developed during the 1990s, first for capillary electrophoresis/electro‐chromatography and later for electrospray ionisation mass spectrometry . More recently, the coupling to matrix‐assisted laser desorption ionisation has been reported . Commercial microfluidic devices for LC/MS applications often comprise of a trapping column, an analytical column and an electrospray ionisation emitter all combined into a single chip design .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid chromatography (LC) devices were later developed during the 1990s, first for capillary electrophoresis/electro‐chromatography and later for electrospray ionisation mass spectrometry . More recently, the coupling to matrix‐assisted laser desorption ionisation has been reported . Commercial microfluidic devices for LC/MS applications often comprise of a trapping column, an analytical column and an electrospray ionisation emitter all combined into a single chip design .…”
mentioning
confidence: 99%
“…[14,15] More recently, the coupling to matrix-assisted laser desorption ionisation has been reported. [16] Commercial microfluidic devices for LC/MS applications often comprise of a trapping column, an analytical column and an electrospray ionisation emitter all combined into a single chip design. [17][18][19] The trapping column allows for the clean up or concentration of a sample before switching it to the analytical column.…”
mentioning
confidence: 99%
“…The IC 50 value is 1.28 lg/ml, which is similar to our previous work (Lee et al 2010b), and the magnitude has small discrepancy with reported results (Pirnia et al 2002;Sagara and Katoh 2000). Full integration with suitable cell culture devices (Hattori et al 2011) or microfluidic based patterning devices (Tsao et al 2010) will provide a useful tool requiring more specific and various combinatorial dilutions of samples for advanced screening and optimization experiments.…”
Section: D Simplex-centroid Screening With Mcf-7 Cellsmentioning
confidence: 99%
“…In one example [56], a COC microfluidic device was developed for contact spotting the outlets of 8 parallel channels to a MALDI plate. Spotting was performed by moving the outlet of these channels within 200 μm of the MALDI plate.…”
Section: Microfluidics Coupled To Maldi-msmentioning
confidence: 99%